Pemanfaatan Teknologi Tepat Guna Untuk Mendorong Peningkatan Hasil Pertanian Melalui Teknologi Aquaponik - Hady, Sultan; Hendrawan, Nalis; Asmiddin, Ahmad Maulid; Azlin, Azlin; Hamid, Helson (Abdimas Indonesian Journal, 2023)
Aquaponics is a food production cultivation system which is a combination of aquaculture and hydroponics. Aquaponic cultivation is cultivation that is conceptually designed based on an excellent ecological recycling system. Food residues and metabolic products in cultivation waste, which are generally considered as pollutants in the environment, can become a source of nutrients through microbial conversion and mineralization and are finally absorbed by vegetable plants in the hydroponic section. The types of plants that are suitable for use in an aquaponics system are leaf vegetables and fruit vegetables. The advantages of using an aquaponic system compared to conventional plant growing mechanisms include a faster growing process, no soil required, can be grown in any location and requires relatively less space, seasonal changes do not affect plant growth, little or no need for herbicides and pesticides, plants remain protected from various diseases. Agricultural products using aquaponic technology in Bahari village can be concluded that the delivery of information has been successful in introducing and educating the public about innovative and sustainable agricultural systems. People now have a better understanding of the basic concept of aquaponics, its benefits, and its working principles in producing food efficiently and sustainably.